Decolonization, dialogue of knowledge and collaborative research: Decolonization, dialogue of knowledge and collaborative research - PÉREZ RUIZ, Maya; ARGUETA VILLAMAR, Arturo (Utopía y Praxis Latinoamericana, 2022)
In this work, elements are proposed for the construction of a collaborative and decolonizing investigation, through a brief review of the conditions that have fostered the continuity of colonial thought and the various forms it assumes. The horizontal and participatory “dialogue of knowledge” is also proposed as a way towards decolonization of thought and the interaction between actors with different knowledge systems, within an ethical framework of respect and justice.